Enhancing knowledge of adolescent mental health among law enforcement: Implementing youth-focused crisis intervention team training. (April 2019) - Kubiak, Sheryl; Shamrova, Daria; Comartin, Erin
Highlights: Feasibility, acceptability, and fidelity criteria were met at the training sites. Short-term outcomes show the majority of officers experienced a positive gain. Curriculum improvements are needed in key areas of the training model. Abstract: This study explores the feasibility, acceptability, fidelity, and outcomes of a youth version of the Crisis Intervention Team training (CIT-Y). This intervention is designed to keep youth with a mental health problem out of the criminal/legal system by equipping police officers with developmentally appropriate information and techniques. Whereas much is known about the adult-focused CIT training, little is known about the youth-focused training. This preliminary investigation uses multiple methods (training observations, officer interviews, and pre/post-tests) to assesses the implementation of CIT-Y in two Midwest counties. Multiple 8-hour training sessions were offered in both counties with 127 officers participating and completing the pre/post measure. The findings of this study confirmed that CIT-Y training was feasible in these counties and acceptable to the officers who participated. Outcomes from the pre/post-tests show that 86% of officers positively changed their knowledge and attitudes regarding youth with mental health problems. Interviews revealed a positive impact on officers' reported behaviors. While this preliminary investigation of CIT-Y showed positive outcomes, recommendations for enhancing the curriculum and subsequent research are discussed.